Point Pelee’s Disappearing Act: Sand Suckers, Erosion, and Conflict Along the Shores of a Canadian National Park - Baxter, Mary (The Northern Mariner / Le marin du nord, 2025)
In the 1900s, residents of Essex County in southern Ontario began to complain to their governments that Point Pelee, a sand spit that extended into Lake Erie, was shrinking. Residents blamed sand suckers, boats that dredged aggregate from water beds for commercial uses; government experts blamed high waters and storms. Both groups’ efforts to determine the source of erosion and address its effects prompted new understandings about the relationship between Great Lakes waterbodies and their water beds and resulted in a permanent ban of the extraction of commercial aggregate from the lake bed surrounding Point Pelee, effectively ending the activity in the Ontario portion of Lake Erie. Using primary sources such as newspaper articles, government reports, and scientific studies, this regional history asserts that Pelee’s plight became a bellwether of the impact of urbanization and industrialization on the Great Lakes and frustration with American economic imperialism impeding Canadian access to domestic resources.